Representación de la mujer indígena en las publicidades de marca Yanbal - Rojas Pulecio, Leonardo Daniel (2021)
This case study will focus on the representation of indigenous women in brand advertising, Yanbal. In order to analyze its image as meaning and importance for this brand. For this, several research techniques will be used to obtain the results. There will also be an interview with one of the representatives who works for this brand, in order to get her point of view on the subject put on the table. The relaunch of the Yanbal brand will also be studied under the “Alma Latina” platform, the one that was announced on June 30, 2021. In addition to applying the interview technique, the signing technique will be applied, where images will be analyzed to find the meaning of its color psychology that the Yanbal brand has used to campaign for this innovative and inclusive idea. Another topic that will be seen below is the launch of the new Ccori Cristal Rosé perfume on the market, represented by a young Peruvian singer named Renata Flores.